Development of a paradigm for studying the effects of brief Goal Management Training with Implementation Intentions. Issue 1 (2nd January 2019) - Baylan, Satu; Evans, Jonathan
ABSTRACT: Cognitive rehabilitation interventions such as Goal Management Training (GMT) and the Implementation Intentions strategy have been developed with the aim of improving prospective memory (PM) in everyday life. The aim of this study was to provide "proof of concept" for an experimental paradigm that could be used to evaluate the effects of Goal Management Implementation Intentions training (GMTii) derived from the principles of GMT and Implementation Intentions. Thirty adults were randomised to either GMTii or a control training condition. A computerised PM task that involved an ongoing task into which a PM task was embedded was completed pre-training and post-training. In addition, a novel yet similar PM task was completed post-training to assess generalisability of any effect. The two groups had similar overall performance pre-training. Post-training, the GMTii group demonstrated significantly better performance on the familiar computerised PM task showing less performance decay over time compared to the control group. The GMTii group also showed better performance on the novel task. The results demonstrated that brief GMTii significantly improved PM performance compared to control training and that computerised PM tasks were sensitive to this effect. The results suggest that this paradigm could be used to study the effects of metacognitive rehabilitation interventions.